2021
DOI: 10.1139/as-2020-0032
|View full text |Cite
|
Sign up to set email alerts
|

From participatory engagement to co-production: modelling climate-sensitive processes in the Arctic

Abstract: Participation is increasingly being used in the modelling of climate-sensitive systems to improve usability. Bottom-up, place-based approaches to modelling can challenge the dominantly positivist approaches used until recently. We examined how participation is reported within modelling research that uses participatory approaches, focusing on the Arctic. Our systematic scoping review identified 26 articles that used participatory approaches in modelling research to explore a climate-sensitive process in an Arct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 92 publications
(107 reference statements)
1
5
0
Order By: Relevance
“…This review shows how PAR has been used in Inuit studies since 2000. The most active PAR users have been Canadians, followed by Americans, a finding in line with the results of two scoping reviews of Arctic participatory research: Brunet et al (2014) and Davies et al (2021, p. 708). In Canada, Indigenous-defined and Indigenous-controlled research approaches have been stimulated since the 1970s by the politicization of Indigenous organizations and their responses to the colonial policies.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…This review shows how PAR has been used in Inuit studies since 2000. The most active PAR users have been Canadians, followed by Americans, a finding in line with the results of two scoping reviews of Arctic participatory research: Brunet et al (2014) and Davies et al (2021, p. 708). In Canada, Indigenous-defined and Indigenous-controlled research approaches have been stimulated since the 1970s by the politicization of Indigenous organizations and their responses to the colonial policies.…”
Section: Discussionsupporting
confidence: 72%
“…When Mosurska and Ford (2020) reviewed the literature of participatory and community-based research in Alaska, particularly on the concepts of community and participation, they concluded that not enough consideration was given to community heterogeneity. Davis, Ford, Quinn, IHACC Research Team, and Harper (2021) conducted a systematic scoping review to identify and evaluate how the participatory approach had been used to model climate-sensitive processes in the Arctic, and to what extent the data collection had been participatory. They found a higher level of participation in studies that favoured non-Western types of knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations